Cylindrical battery, battery can for cylindrical battery, and method for manufacturing cylindrical battery

JP7630933B2Active Publication Date: 2025-02-18FDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020121144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-15
Publication Date
2025-02-18
Estimated Expiration
2040-07-15

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、電極合剤を電池缶に圧入する際の電極合剤の破損や導電膜の剥離を抑止できる筒形電池、筒形電池用電池缶、および筒形電池の製造方法が提供される。その他の効果につては以下の記載で明らかにする。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630933000004
    Figure 0007630933000004
  • Figure 0007630933000005
    Figure 0007630933000005
  • Figure 0007630933000006
    Figure 0007630933000006
Patent Text Reader

Abstract

To provide a cylindrical battery that can prevent damage to an electrode mixture and peeling of a conductive film when the electrode mixture is press-fitted into a battery can.SOLUTION: A cylindrical battery 1 has an electrode mixture 3 made of a compact pressed into a battery can 2, which also serves as a current collector. The battery can has a plurality of conductive films (10a, 10b), which are formed in layers from an inner surface 2i toward the inner radial direction. The plurality of conductive films includes a first conductive film formed in contact with the inner surface and a second conductive film formed on the side in contact with the electrode mixture and having superior lubricity to the first conductive film.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cylindrical battery, a battery can for a cylindrical battery, and a method for manufacturing a cylindrical battery. [Background technology]

[0002] There is a type of battery structure called the inside-out type. In the inside-out type battery, an electrode mixture made of a compact compressed using a mold or the like is pressed into a battery can that also serves as a current collector. As a cylindrical battery, for example, a cylindrical alkaline battery and a bobbin-type nonaqueous electrolyte battery described in the following Patent Document 1 are well known.

[0003] As an example of a cylindrical battery, a cylindrical alkaline battery 1 is shown in Figure 1. Figure 1 shows an LR6 type alkaline battery 1, with Figure 1(A) being a vertical cross-sectional view when the extension direction of the cylindrical axis 50 is the up-down (vertical) direction, and Figure 1(B) being an enlarged view of the area within a circle 100 in Figure 1(A).

[0004] As shown in Fig. 1(A), an alkaline battery 1 is composed of a cylindrical metal battery can 2 with a bottom, a ring-shaped positive electrode mixture (hereinafter referred to as positive electrode mixture 3), a cylindrical separator 4 with a bottom disposed inside the positive electrode mixture 3, a negative electrode gel 5 containing a zinc alloy filled inside the separator 4, a metallic negative electrode current collector 6 inserted into the negative electrode gel 5, a dish-shaped metallic negative electrode terminal plate 7, and a resin sealing gasket 8. In this structure, the positive electrode mixture 3, the separator 4, and the negative electrode gel 5 form a power generating element of the alkaline battery 1 in the presence of an electrolyte. In the following figures including Fig. 1, the top and bottom directions are defined with the bottom side of the battery can 2 as the bottom.

[0005] As shown enlarged in FIG. 1(B), a conductive film 10 formed by applying a conductive paint is formed on the inner surface 2i of the battery can 2, at least over a region 20 in which the positive electrode mixture 3 is disposed. The positive electrode mixture 3 is inserted in a press-fit state into the battery can 2, and the battery can 2 functions as a positive electrode current collector by contacting the inner surface 2i with the outer peripheral surface 3o of the positive electrode mixture 3 via the conductive film 10. The conductive film 10 is provided to reduce contact resistance between the outer peripheral surface 3o of the annular positive electrode mixture 3 and the inner surface 2i of the battery can 2. Note that the alkaline battery 1 shown in the figure has three positive electrode mixtures 3 stacked vertically in the battery can 2.

[0006] A positive electrode terminal 9 is formed so as to protrude downward at the bottom end of the battery can 2. The dish-shaped negative electrode terminal plate 7 is dish-shaped with a flange-like edge, and is crimped to the opening of the battery can 2 via a sealing gasket 8 with the dish facing down when the positive electrode terminal 9 is facing downward.

[0007] The rod-shaped negative electrode current collector 6 inserted in the negative electrode gel 5 has a disk-shaped head 61 at its upper end, and a rod-shaped body 62 extending downward is integrally formed on the lower surface of the head 61, and the upper surface 63 of the head 61 is welded to the lower surface 71 of the dish-shaped negative electrode terminal plate 7, and is fixed in an upright state in the battery can 2. The negative electrode terminal plate 7, the negative electrode current collector 6, and the sealing gasket 8 are previously combined together as a sealing body, and the sealing gasket 8 is sandwiched between the opening edge of the battery can 2 and the flange-shaped edge of the negative electrode terminal plate 7 to seal the battery can 2. The structure and manufacturing procedure of a typical cylindrical alkaline battery are described in the following Non-Patent Document 1. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2001-273911 A [Non-patent literature]

[0009] [Non-Patent Document 1] FDK Corporation, "How alkaline batteries are made", [online], [searched June 15, 2020], Internet<URL:http: / / www.fdk.co.jp / denchi_club / denchi_story / arukari.htm> Summary of the Invention [Problem to be solved by the invention]

[0010] As described above, in an inside-out cylindrical battery, a conductive film is formed on the inner surface of the battery can. The conductive paint used for the conductive film is a powdered conductive material such as graphite dispersed in a solvent. The conductive film is formed by volatilizing the solvent from the conductive paint applied to the inner surface of the battery can, causing the dried powdered conductive material to adhere to the inner surface of the battery can.

[0011] However, in conventional cylindrical batteries, the frictional resistance between the outer surface of the electrode mixture and the conductive film formed on the inner surface of the battery can is large, and when the electrode mixture is pressed into the battery can, damage such as chipping may occur on the outer surface of the electrode mixture. In addition, friction when the electrode mixture is pressed into the battery can may cause a part of the conductive film to peel off. And, if a part of the electrode mixture is damaged or a part of the conductive film is peeled off in the region where the battery can and the electrode mixture contact each other, the contact resistance between the battery can and the electrode mixture increases at the location where the damage or peeling occurs. And, in conventional cylindrical batteries, the above-mentioned damage to the electrode mixture and peeling of the conductive film were one of the factors that hinder the improvement of discharge performance, especially discharge performance during high-load discharge.

[0012] Therefore, an object of the present invention is to provide a cylindrical battery, a battery can for a cylindrical battery, and a method for manufacturing a cylindrical battery that can prevent damage to the electrode mixture and peeling of the conductive film when the electrode mixture is pressed into the battery can. [Means for solving the problem]

[0013] One aspect of the present invention for achieving the above object is a cylindrical battery in which an electrode mixture made of a molded body is pressed into a battery can that also serves as a current collector, the battery can has a plurality of conductive films formed in layers from an inner surface toward a radially inward direction, The plurality of conductive films include a first conductive film formed in contact with the inner surface and a second conductive film formed on the side in contact with the electrode mixture. The second a conductive film; the first conductive film is a dried conductive film formed by adhering a powdered carbon material; The second conductive film is a gel-like conductive film having superior lubricity to the first conductive film.

[0014] Another aspect of the present invention is a cylindrical battery in which an annular electrode mixture is pressed into a battery can that also serves as a current collector, The conductive film has a plurality of layers formed from the inner surface toward the radially inward direction, The plurality of conductive films include a first conductive film formed in contact with the inner surface and a second conductive film formed on the surface side in the radial inward direction. The second a conductive film; the first conductive film is a dried conductive film formed by adhering a powdered carbon material; The second conductive film is a second gel-like conductive film that has superior lubricity to the first conductive film.

[0015] In addition, one aspect of the present invention also includes a method for manufacturing a cylindrical battery in which an annular electrode mixture is pressed into a cylindrical battery can that also serves as a current collector, the method comprising the steps of: The battery can is a cylindrical battery can having an opening at the top and a bottom, and the inner surface of the battery can is coated with a conductive powder. material depositing a first conductive film comprising: The battery can The second on the inside A conductive material application step of applying a conductive material, which is a source of a conductive film, in a circular shape around an axis of the cylindrical battery can; a mixture injection step of injecting the electrode mixture into the battery can by pressure, the mixture being followed by the conductive material application step; Including, In the mixture press-in step, the electrode mixture is pressed into the battery can by an outer peripheral surface of the electrode mixture. The origin of the second conductive film The second conductive film is formed by applying a conductive material to the surface layer of another conductive film already formed on the inner surface of the battery can while causing the conductive material to flow on the surface layer. Effect of the Invention

[0016] According to the present invention, there are provided a cylindrical battery, a battery can for a cylindrical battery, and a manufacturing method for a cylindrical battery, which are capable of preventing damage to the electrode mixture and peeling of the conductive film when the electrode mixture is pressed into the battery can. Other effects will be made clear in the following description. [Brief description of the drawings]

[0017] [Figure 1] 1 is a diagram showing the structure of a cylindrical alkaline battery, which is an example of a cylindrical battery. [Diagram 2] 4A and 4B are diagrams showing the structure of a conductive film formed on the inner surface of a battery can of a cylindrical battery according to an embodiment of the present invention. [Diagram 3] 5A to 5C are diagrams showing a procedure for forming a gelled conductive film that constitutes the conductive film of the cylindrical battery according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The embodiments of the present invention will be described with reference to the accompanying drawings. In the drawings used in the following description, the same or similar parts may be designated by the same reference numerals, and duplicated explanations may be omitted. If a part designated by a reference numeral in one drawing is unnecessary, the same part may not be designated by a reference numeral in other drawings.

[0019] An LR6 alkaline battery is taken as an example of a cylindrical battery according to an embodiment of the present invention. The basic configuration and appearance of the cylindrical battery according to the embodiment are similar to that of a general alkaline battery 1 shown in FIG. 1. However, the cylindrical battery according to the embodiment (hereinafter sometimes referred to as "alkaline battery 1") is characterized by the structure of a conductive film 10 formed on the inner surface 2i of a battery can 2, which can prevent damage to the positive electrode mixture 3 when the positive electrode mixture 3 is pressed into the battery can 2 during the manufacturing process, and also reduces the contact resistance between the positive electrode mixture 3 and the inner surface 2i of the battery can 2, resulting in excellent discharge characteristics.

[0020] FIG. 2 shows the structure of the conductive film 10 formed on the inner surface 2i of the battery can 2 of the alkaline battery 1. FIG. 2 corresponds to the area within the circle 100 in FIG. 1. As shown in FIG. 2, the conductive film 10 is formed in layers on the inner surface 2i of the battery can 2 of the alkaline battery 1 from the inner surface 2i toward the axis 50 of the battery can 2, that is, toward the radially inward direction of the battery can 2. In this embodiment, a two-layer conductive film 10 is formed, and a conductive film (hereinafter sometimes referred to as a powdered conductive film 10a) made by attaching a powdered carbon material is formed on the side in contact with the inner surface 2i of the battery can 2, as in the conventional alkaline battery 1, and a conductive film 10b having excellent lubricity relative to the powdered conductive film 10a is formed on the surface layer side (the inner side of the battery can 2) in contact with the outer peripheral surface 3o of the positive electrode mixture 3. In this embodiment, a gel-like conductive film (hereinafter sometimes referred to as a gel-like conductive film 10b) is formed. In FIG. 2, the thickness of the conductive films (10, 10a, 10b) is exaggerated relative to the thickness of the battery can 2 in order to make the structure of the conductive film 10 easier to understand.

[0021] Next, in order to evaluate the characteristics of the alkaline battery 1 of this embodiment, various LR6 type alkaline batteries were produced as samples, each having a different state of formation of the conductive film 10. Table 1 below shows the state of formation of the conductive film 10 in each sample.

[0022] [Table 1] As shown in Table 1, Sample 1 is an alkaline battery 1 according to the embodiment, and has a two-layer conductive film 10 as shown in Fig. 2. Sample 2 is a conventional alkaline battery 1, in which only a powder-like conductive film 10a is formed on the inner surface 2i of the battery can 2. Sample 3 is a battery can 2 in which only a gel-like conductive film 10b is formed on the inner surface 2i of the battery can 2, and Sample 4 is a battery can 2 in which no conductive film 10 is formed on the inner surface 2i of the battery can 2.

[0023] The powdered conductive films 10a in Samples 1 and 2 were both formed under the same conditions, by spraying a conductive paint made of a mixture of powdered graphite as a conductor and MEK as a solvent in a mass ratio of 50:50 onto the inner surface 2i of the battery can 2, and then drying (volatilizing the solvent). The conductor contained in the powdered conductive films 10a has a dry weight of 5 mg or more.

[0024] On the other hand, the gelled conductive films 10b in Samples 1 and 3 were both formed under the same conditions and consisted of a conductive material (hereinafter sometimes referred to as gelled conductive material) in which graphite, polyacrylic acid (PA) as a gelling agent, KOH as an electrolyte, and water as a diluent were mixed in mass ratios of 65%, 1%, 12%, and 22%, respectively. Note that 10 mg or more of the gelled conductive material was used to form the gelled conductive film 10b.

[0025] The gelled conductive film 10b may be formed by applying a gelled conductive material to the inner surface 2i of the battery can 2 using a brush or the like, but in Samples 1 and 3, the gelled conductive film 10b is formed simultaneously with the process of pressing the positive electrode mixture 3 into the battery can 2 by utilizing the viscosity and fluidity of the gelled conductive material. The procedure for forming the gelled conductive film 10b is shown in Fig. 3. Fig. 3(A) and Fig. 3(B) show vertical cross-sectional views of the battery can 2 before sealing, and Fig. 3(C) is an enlarged view of the inside of a circle 101 in Fig. 3(B).

[0026] First, as shown in FIG. 3(A), on the inner surface 2i of the battery can 2 before sealing, in the state of the assembled alkaline battery 1 (see FIG. 1), the gelled conductive material 10c is applied in a ring shape to the upper end position 3u of the region 20 facing the outer peripheral surface 3o of the positive electrode mixture 3. Next, as shown by the thick arrow in FIG. 3(B), the positive electrode mixture 3 is pressed downward from the open end of the battery can 2. As a result, for example, in the case of sample 3, as shown in FIG. 3(C), the applied gelled conductive material 10c flows downward in the battery can 2 and is applied to the inner surface 2i of the battery can 2 to form the gelled conductive film 10b. In the case of sample 1, the gelled conductive material 10c is applied to the surface layer of the powdered conductive film 10a already formed on the inner surface 2i of the battery can 2 to form the gelled conductive film 10b.

[0027] For Samples 1 to 3 in which the conductive film 10 was formed by the above-mentioned procedure, and Sample 4 in which the conductive film 10 was omitted, the friction characteristics when the positive electrode mixture 3 was pressed into the battery can 2 during the manufacturing process were first examined in terms of the slipperiness of the positive electrode mixture 3, the presence or absence of damage such as chipping or cracking of the positive electrode mixture 3, and the presence or absence of peeling of the powdery conductive film 10a. The friction characteristics for each sample are shown in Table 2 below.

[0028] [Table 2] In Table 2, various friction characteristics of Sample 2 corresponding to conventional alkaline battery 1 are used as the standard, and the standard is indicated by "△" in the table. Also, in Table 2, the sliding characteristics indicate the ease of pressing the positive electrode mixture 3 into the battery can 2, and in Sample 2, the case where the positive electrode mixture 3 could be pressed into the battery can 2 at a pressure lower than the pressure required for pressing the positive electrode mixture 3 is indicated by "◯", and the case where a pressure higher than the standard was required for pressing the positive electrode mixture 3 is indicated by "X".

[0029] In addition, regarding the damage of the positive electrode mixture 3, multiple samples (for example, 100 pieces) were prepared for each sample, and the frequency of defects such as chipping or cracking of the positive electrode mixture 3 when the positive electrode mixture 3 was pressed into the battery can 2 was indicated by "△", "◯", or "×". In the table, the frequency of defects in sample 2 was used as the standard, and samples in which defects occurred but the frequency was below the standard were indicated by "△". In addition, samples in which no defects occurred in any of the samples were indicated by "◯". Samples in which the number of defects was greater than the standard were indicated by "×". The damage of the positive electrode mixture 3 was examined by checking whether there was a defect before all three positive electrode mixtures 3 equipped in the alkaline battery 1 were pressed in. The damage of the positive electrode mixture 3 can be visually confirmed when the positive electrode mixture 3 is pressed into the battery can 2. Not only the cracking of the positive electrode mixture 3, but also the occurrence of a defect when part of the positive electrode mixture 3 is chipped can be confirmed by checking whether or not there is a piece of the positive electrode mixture 3 that has fallen into the battery can 2.

[0030] In Table 2, the peeling of the powdered conductive film 10a was indicated by "△", "○", or "×" according to the number of individuals in which a defect occurred, similar to the damage of the positive electrode mixture 3, by preparing multiple individuals for each sample. Sample 3 having only the gelled conductive film 10b and sample 4 having no conductive film 10 were not evaluated, and are therefore indicated by "-" in the table. If peeling of the powdered conductive film 10a occurs above the pressed positive electrode mixture 3 by the time the second positive electrode mixture 3 is pressed in, the peeling can be visually confirmed by observing the inner surface 2i of the battery can 2. The inner surface 2i of the battery can 2 is exposed at the location where the powdered conductive film 10a peeled off. For individuals in which peeling of the powdered conductive film 10a was not confirmed at the time the second positive electrode mixture 3 was pressed in, the battery can 2 was cleaved after all three positive electrode mixtures 3 were pressed in to the battery can 2, and the presence or absence of peeling of the powdered conductive film 10a was confirmed.

[0031] As shown in Table 2, in samples 1 and 3 in which the gelled conductive film 10b is in contact with the outer peripheral surface 3o of the positive electrode mixture 3, the slipperiness of the positive electrode mixture 3 was good, and no damage to the positive electrode mixture 3 occurred. In addition, in sample 1 having the conductive film 10 of a two-layer structure, peeling of the powdered conductive film 10a did not occur. In addition, in sample 4 in which the conductive film 10 is not formed on the inner surface 2i of the battery can 2, a metal surface made of nickel plating or the like is exposed on the inner surface 2i of the battery can 2. In this sample 4, the slipperiness of the positive electrode mixture 3 was worse than that of sample 2, which is a conventional alkaline battery 1, and the positive electrode mixture 3 was also easily damaged. Therefore, it was confirmed from the friction characteristics of this sample 4 that the friction of the metal surface is greater than that of the powdered conductive film 10a.

[0032] For the above reasons, at least in an inside-out type cylindrical battery 1, if the gelled conductive film 10b is formed so as to contact the outer peripheral surface 3o side of the positive electrode mixture 3, the lubricity of the positive electrode mixture 3 is improved, and the productivity of the cylindrical battery 1 can be improved. In addition, damage to the positive electrode mixture 3 does not occur, and the yield is improved.

[0033] Next, the discharge performance of each sample was evaluated based on the initial characteristics immediately after assembly and the post-storage characteristics after storage at a temperature of 60° C. for 100 days after assembly. For the evaluation of discharge performance, an individual was used in which the positive electrode mixture 3 was not damaged when the positive electrode mixture 3 was pressed into the battery can 2 and no peeling occurred in the powdered conductive film 10a when the second positive electrode mixture 3 was pressed in. Then, for each sample, a predetermined number of individuals (for example, 10 pieces) were prepared for each of the initial characteristics and post-storage characteristics, and the discharge characteristics were evaluated by performing a discharge test in accordance with the JIS C8515:2017 standard.

[0034] Specifically, the discharge performance was evaluated by the time it took to reach a predetermined end voltage in three different discharge modes. The three discharge modes were for evaluating the light load discharge performance, the medium load discharge performance, and the heavy load discharge performance, respectively. The light load discharge performance was evaluated in a discharge mode in which the end voltage was set to 0.8V and a load of 3.9Ω was applied and discharged for one hour per day. The medium load discharge performance was evaluated in a discharge mode in which the end voltage was set to 0.9V and discharged for one hour at a current of 250mA per day. The heavy load discharge performance was evaluated in a discharge mode in which the end voltage was set to 1.05V and an alternating discharge operation of discharging 1500mW of power for two seconds, followed by discharging 650mW of power for 28 seconds, was continuously repeated for five minutes, followed by a 55-minute pause in discharging. The discharge performance of each sample was evaluated by the average value of the individuals belonging to each sample. The discharge performance of each sample is shown in Table 3 below.

[0035] [Table 3] In Table 3, the initial characteristics of sample 2 corresponding to conventional alkaline battery 1 are used as the standard, and those that were less than ±5% from this standard are marked with "○", those that were improved by 5% or more are marked with "◎", those that were deteriorated by 5% or more are marked with "△", and those where discharge operation itself was impossible are marked with "×". As shown in Table 3, the post-storage characteristics of sample 2 showed that only the light-load discharge performance maintained the initial characteristics, while the medium-load discharge performance and heavy-load discharge performance deteriorated.

[0036] On the other hand, in the case of Sample 1 corresponding to the alkaline battery 1 of the embodiment, the initial characteristics showed improved discharge performance under all conditions, including light, medium, and heavy loads. As for the post-storage characteristics, the discharge performance under light and medium loads was also improved, and the heavy load discharge performance was equivalent to the initial characteristics of Sample 2.

[0037] In addition, in sample 3 having only the gelled conductive film 10b and sample 4 not having the conductive film 10, only the light load discharge performance met the standard in the initial characteristics, and the medium load discharge performance was deteriorated. Moreover, the heavy load discharge performance in the initial characteristics and all discharge performance in the characteristics after storage were not dischargeable.

[0038] From the above, it was found that the gel-like conductive film 10b has a higher surface resistivity than the powder-like conductive film 10a. Nevertheless, in Sample 1 in which the gel-like conductive film 10b is interposed between the powder-like conductive film 10a and the positive electrode mixture 3, the discharge performance is not equal to, but clearly improved from, Sample 2 in which only the powder-like conductive film 10a is present.

[0039] The reason for the improved discharge performance in Sample 1 is believed to be that the gelled conductive film 10b protects the powdered conductive film 10a and prevents peeling of the powdered conductive film 10a when the positive electrode mixture 3 is pressed into the battery can 2. However, since the discharge performance of Sample 1 is significantly improved compared to Sample 2, it is difficult to believe that the improvement in discharge performance in Sample 1 is solely due to the prevention of peeling of the powdered conductive film 10a.

[0040] Incidentally, it is known that there are many microscopic recesses on the surface of the positive electrode mixture 3 that occur during molding, and it can be considered that in the sample 1 having the conductive film 10 with a two-layer structure, the gel conductive film 10b fills these recesses, thereby improving the discharge performance. That is, in the sample 1, the entire surface of the outer circumferential surface 3o of the positive electrode mixture 3 and the inner surface 2i of the battery can 2 are securely adhered to each other between all layers of the two-layer conductive film 10 and the inner surface 2i of the battery can 2, and the increase in contact resistance that has conventionally occurred due to the recesses is suppressed, and as a result, it can be considered that the discharge performance is improved compared to the sample 2. Of course, in the alkaline battery 1 according to the embodiment, even if there are fine protrusions on the outer circumferential surface 3o of the positive electrode mixture 3, the outer circumferential surface 3o is leveled by the fluid gel conductive film 10b, so it is easily expected that the deterioration of the discharge performance caused by the protrusions on the outer circumferential surface 3o of the positive electrode mixture 3 can also be suppressed.

[0041] On the other hand, in sample 2 corresponding to the conventional alkaline battery 1, the outer peripheral surface 3o of the positive electrode mixture 3 is in contact with the powdered conductive film 10a in a recessed state. Therefore, at the locations of the recesses, the conductive particles such as graphite constituting the powdered conductive film 10a cannot come into contact with the outer peripheral surface 3o of the positive electrode mixture 3, which makes it difficult to improve the discharge performance.

[0042] As described above, in the alkaline battery 1 according to the embodiment, the powdered conductive film 10a and the gelled conductive film 10b are formed in this order on the inner surface 2i of the battery can 2 radially inward from the inner surface 2i, and thus the positive electrode mixture 3 can be easily pressed into the battery can 1 during the manufacturing process, thereby improving productivity. In addition, in the alkaline battery 1 according to the embodiment, the gelled conductive material 10c constituting the gelled conductive film 10b functions as a lubricant when the positive electrode mixture 3 is pressed into the battery can 2, and the powdered conductive film 10a, which contributes most to reducing the internal resistance of the alkaline battery 1, is unlikely to peel off. Furthermore, in the alkaline battery 1 according to the embodiment, the gelled conductive film 10b is filled into minute recesses present on the outer peripheral surface 3o of the positive electrode mixture 3. As a result, the alkaline battery 1 according to the embodiment has excellent discharge performance.

[0043] In the alkaline battery 1 according to the embodiment, the layered conductive film 10 formed on the inner surface 2i of the battery can 2 has a gel-like conductive film 10b with excellent lubricity formed on the side in contact with the outer peripheral surface 3o of the positive electrode mixture 3, but the conductive film 10b on the surface side of the conductive film 10 does not have to be gel-like. The conductive film 10b on the surface side may be, for example, a conductive material made of ultrafine particles such as fullerene formed in a film shape in the same manner as the powdered conductive film 10a. In any case, it is sufficient that the conductive film 10b with excellent lubricity relative to the powdered conductive film 10a is formed on the surface side of the layered conductive film 10. This reduces the frictional resistance when the positive electrode mixture 3 is pressed into the battery can 2, and prevents damage to the positive electrode mixture 3 and peeling of the powdered conductive film 10a. In addition, if the conductive film 10b is made of ultrafine particles, it is more likely that the ultrafine particles fill the recesses present on the outer peripheral surface 3o of the electrode mixture 3, thereby preventing an increase in the contact resistance between the electrode mixture 3 and the inner surface 2i of the battery can 2. The layered conductive film 10 does not have to be two-layered, and may be three or more layers long as it has a powdered conductive film 10a in contact with the inner surface 2i of the battery can 2 and a conductive film 10b in contact with the outer peripheral surface 3o of the positive electrode mixture 3 and having better lubricity than the powdered conductive film 10a.

[0044] The cylindrical battery 1 according to the embodiment is not limited to a cylindrical alkaline battery 1, so long as the annularly compressed electrode mixture is in contact with the inner surface 2i of the battery can 2 so that the battery can 2 functions as a current collector. [Explanation of symbols]

[0045] 1 Cylindrical battery (alkaline battery), 2 Battery can (positive electrode can), 2i Inner surface of battery can, 3 positive electrode mixture, 3o outer surface of positive electrode mixture, 4 separator, 5 negative electrode gel, 6 negative electrode current collector, 7 negative electrode terminal plate, 8 sealing gasket, 9 positive electrode terminal, 10 Conductive film, 10a Powdered conductive film, 10b Conductive film with excellent lubricity (gel-like conductive film), 50 Cylinder shaft

Claims

1. A cylindrical battery in which an electrode mixture made of a molded body is pressed into a battery can that also serves as a current collector, the battery can has a plurality of conductive films formed in layers from an inner surface toward a radially inward direction, the plurality of conductive films include a first conductive film formed in contact with the inner surface and a second conductive film formed on a side in contact with the electrode mixture, the first conductive film is a dried conductive film formed by adhering a powdered carbon material; the second conductive film is a gel-like conductive film having superior lubricity to the first conductive film; Cylindrical battery.

2. 2. The cylindrical battery according to claim 1, comprising a two-layer conductive film consisting of the first conductive film and the second conductive film.

3. A cylindrical battery can in which an annular electrode mixture is pressed into a battery can that also serves as a current collector, The conductive film has a plurality of layers formed from the inner surface toward the radially inward direction, the plurality of conductive films include a first conductive film formed in contact with the inner surface and a second conductive film formed on a surface side in a radial inward direction, the first conductive film is a dried conductive film formed by adhering a powdered carbon material; the second conductive film is a second gel-like conductive film having superior lubricity to the first conductive film; Battery can for cylindrical batteries.

4. A method for manufacturing a cylindrical battery in which an annular electrode mixture is pressed into a cylindrical battery can that also serves as a current collector, comprising: A step of attaching a first conductive film made of a powdered conductive material to an inner surface of the battery can having a cylindrical shape with a bottom and an opening at the top; a conductive material application step of applying a conductive material, which is a source of a second conductive film, to an inner surface of the battery can in a circular shape around an axis of the cylindrical battery can; a mixture injection step of injecting the electrode mixture into the battery can by pressure, the mixture being followed by the conductive material application step; Including, In the mixture press-in step, a conductive material that is the source of the second conductive film is caused to flow on a surface layer of another conductive film already formed on the inner surface of the battery can by an outer peripheral surface of the electrode mixture being pressed into the battery can, and the second conductive film is formed by applying the conductive material to the surface layer. A method for manufacturing cylindrical batteries.

Citation Information

Patent Citations

  • Alkaline cell

    JP1985257070A

  • Bobin type non-electrolytic solution battery

    JP2001273911A

  • Manufacturing method of battery

    JP2001291521A

  • Battery can and alkaline battery using it

    JP2007026865A

  • Positive electrode mixture for alkaline battery and inside-out type alkaline battery

    JP2017068905A